Caste : the origins of our discontents : adapted for young adults - Wilkerson, Isabel (Delacorte Press, 2022)
"This work is based on Caste: The Origins of Our Discontents, copyright © 2020 by Isabel Wilkerson. Originally published in the United States in hardcover by Random House, an imprint and division of Penguin Random House LLC"--